A study on the relation between socio-economic characteristics and HIV/AIDS among the tribal women of Jaintia Hills, Meghalaya (Indian Journal of Forensic Medicine & Toxicology, 2020)
The social fabric of a population is of utmost importance to know the scenario of HIV/AIDS in thatpopulation. This paper highlights vulnerability of women towards the disease based on their socio-economiccharacteristics. It is a cross-sectional study among the Jaintia tribal women of Meghalaya belonging to thereproductive and vulnerable age group (15-35years). The methods used for data collection are structuredinterview schedules, participant observation, focussed group discussions and in-depth interviews. Thefindings revealed that majority of the women are poor and uneducated and as a result, this has an impact ontheir role and ability to protect them from contracting the disease.